2009
DOI: 10.1111/j.1365-294x.2009.04437.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome scan in the mosquito Aedes rusticus: population structure and detection of positive selection after insecticide treatment

Abstract: Identification of genes involved in local adaptation is particularly challenging for species functioning as a network of interconnected populations undergoing frequent extinctions-recolonizations, because populations are submitted to contrasted evolutionary pressures. Using amplified fragment length polymorphism markers, population genetic structure of the mosquito Aedes rusticus was analysed in five geographical areas of the French Rhône-Alpes region. We included a number of sites that were treated with the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 77 publications
(142 reference statements)
3
54
0
Order By: Relevance
“…As no decrease in the expected heterozygosity and genotypic diversity was detected in the commercial area, we argue that the population size inside this area remains large enough to avoid the occurrence of a genetic drift effect. Alternatively, gene flow from the outside to the inside of the commercial plantation might continuously restore genetic diversity, as was suggested in the case of the mosquito Aedes rusticus when sites treated with bioinsecticides were compared with non-treated sites (Paris et al, 2010). The occurrence of sexual reproduction in M. fijiensis in commercial plantations is limited, mainly because of regular elimination of the necrotic tissues where sexual ascospores are produced.…”
Section: Discussionmentioning
confidence: 99%
“…As no decrease in the expected heterozygosity and genotypic diversity was detected in the commercial area, we argue that the population size inside this area remains large enough to avoid the occurrence of a genetic drift effect. Alternatively, gene flow from the outside to the inside of the commercial plantation might continuously restore genetic diversity, as was suggested in the case of the mosquito Aedes rusticus when sites treated with bioinsecticides were compared with non-treated sites (Paris et al, 2010). The occurrence of sexual reproduction in M. fijiensis in commercial plantations is limited, mainly because of regular elimination of the necrotic tissues where sexual ascospores are produced.…”
Section: Discussionmentioning
confidence: 99%
“…A major point to address today is thus how to further improve the product and even more importantly how to make it sustainable. In natural mosquito populations, no consistent resistance has been detected even after long periods of repeated treatment with Bti toxins, but recent studies suggested that moderate Bti resistance may occur locally (Paul et al, 2005;Boyer et al, 2007;Paris et al, 2010). Furthermore, we obtained in only 22 generations of selection using environmental Bti (i.e., field collected leaf litters containing Bti toxins), a strain of Ae.…”
Section: Evolution Of Bti Resistance In Mosquitoesmentioning
confidence: 96%
“…Resistance to Bti can involve both mutations (in specific proteases, specific membrane receptors), transcriptional regulation (up or down regulation of proteases, of membrane receptors and other co-factors involved in toxin binding, of immune genes…) and post-transcriptional changes (alternative splicing of mRNA…). Given the variety of mechanisms involved in resistance to the multiple toxin contained in Bti, a global screening of genomic /transcriptomic/ proteomic changes in resistant insects should be favoured to a candidate gene approach, in order to tackle all the genes simultaneously involved and their interactions (Bonin et al, 2008, 2009, Paris et al, 2010. Bti containing a mixture of toxins with various modes of action, the resistance is likely to involve many loci with various levels of dominance and various degrees of epistatic interactions.…”
Section: The Genetic Basis Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The first step of an investigation of genetic markers that may signal local adaptation is usually to determine if some loci in a dataset are correlated with local habitat or climatic conditions (Eckert et al 2010a;Paris et al 2010;Poncet et al 2010;Nunes et al 2011). While population genomics can give us valuable clues for which genes are of ecological relevance, a more specific approach, using phenotype, can indicate which genes may be associated with fitnessrelated phenotypic traits, such as in using QTLs (Shaw et al 2007;Lacaze et al 2009;Du et al 2016;McCouch et al 2016).…”
Section: The Use Of Phenotype In Studies On Local Adaptationmentioning
confidence: 99%